2014
DOI: 10.1097/cad.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

TCF4 silencing sensitizes the colon cancer cell line to oxaliplatin as a common chemotherapeutic drug

Abstract: Colon cancer is among the most prevalent cancers worldwide. Although the main modality of treatment is surgery, resistance to chemoradiotherapy raises concerns. Hence, we aimed to determine the effect of RNA-mediated silencing of tcf4, the downstream effector of the wnt signaling pathway, on the response of the SW480 cell line to oxaliplatin, a common chemotherapeutic drug. For this, two different silencing sequences against TCF4 mRNA were selected and cloned into pSilencer neo2.1. The SW480 cell line was stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…DIO2 encoded the type II iodothyronine deiodinase (31) and is associated with the carcinogenesis in mesothelioma (32) and malignant thyroid tumors (33). In addition, the silencing TCF4, which is known as immunoglobulin transcription factor 2 (34), sensitize the colon cancer (35). Furthermore, IL-15 is well known as a cytokine associated anti-cancer effects (36).…”
Section: Resultsmentioning
confidence: 99%
“…DIO2 encoded the type II iodothyronine deiodinase (31) and is associated with the carcinogenesis in mesothelioma (32) and malignant thyroid tumors (33). In addition, the silencing TCF4, which is known as immunoglobulin transcription factor 2 (34), sensitize the colon cancer (35). Furthermore, IL-15 is well known as a cytokine associated anti-cancer effects (36).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicated that TCF4 functions to promote cellular proliferation (44,45). TCF4 silencing sensitizes the CRC line to L-OHP as a common chemotherapeutic drug (46). Hereby, TCF4 was related to hsa-miR-606, -381 and -429.…”
Section: Discussionmentioning
confidence: 95%
“…There are some data that support this hypothesis by showing that blocking Lgr5 expression using inhibitory RNA increases the chemosensitivity of colon cancer cells and that overexpression of Lgr5 is correlated with chemoresistance, presumably through the control of promoters for multidrug resistance-determining transporters like ABCB1 [4][5][6]. As Wnt/β-catenin signaling is required to support stemness, inhibition of Wnt signaling is expected to increase the sensitivity of CRC cells to cytotoxic therapy; indeed, supporting data were obtained by some researchers [7,8]. Other authors, however, have discovered that Lgr5-expressing cells are more sensitive to anticancer drugs [9,10].…”
Section: Introductionmentioning
confidence: 58%
“…This is why cell culture work and immunohistochemical analysis of genes that are influenced by Lgr5 expression are of paramount importance. Considering the Wnt signaling-dependent mechanism of some Lgr5 functions, it is noteworthy that inhibition of Tcf4 expression sensitizes SW480 cells to oxaliplatin by inducing apoptosis [8]. The mechanism of sensitization by Lgr5 needs further investigation.…”
Section: Discussionmentioning
confidence: 99%